Analyzing the Correlation between Psychosocial Factor and Happiness Among Millennial Workers in PT. Kereta Api Indonesia Head Office - Mahmudah, Agisti Handayani; Ginting, Henndy (Journal of Business and Management, 2019)
Abstract. Nowadays, in the globalization era, millennials are the largest generation that occupying several roles in the company. Millennial employees have become a problem for almost companies because most of them have a hard to retain Millennials in the company. Millennial employees will leave their jobs if they are feel depressed and unhappy with their work. One of the important things to keep Millennial employees in the company is happiness at work. Psychosocial factors are elements that influence employees' happiness response to working conditions, which can potentially cause psychological health. This study analyzed the correlation between psychosocial factors and happiness. There are 10 psychosocial factor analyzed in this research. The data of this research has been collected by using descriptive statistics and Moderated Linear Regression method for statistical analytics. The result of this research shows that sense of community is experiencing psychosocial factors and that has a positive impact among other psychosocial factors. The happiness index level in PT. Kereta Api Indonesia Head Office in average is in Medium Level with 72,3%. And the most correlated psychosocial factor for happiness in millennial workers is organizational justice. It can be concluded that psychosocial factors have a correlation with the level of happiness for millennial workers at PT. Kereta Api Indonesia Head Office. Keyword:  Happiness, Happiness Index, Millennial generation, Psychosocial factors, PT. Kereta Api Indonesia Head Office. Abstract. Nowadays, in the globalization era, millennials are the largest generation that occupying several roles in the company. Millennial employees have become a problem for almost companies because most of them have a hard to retain Millennials in the company. Millennial employees will leave their jobs if they are feel depressed and unhappy with their work. One of the important things to keep Millennial employees in the company is happiness at work. Psychosocial factors are elements that influence employees' happiness response to working conditions, which can potentially cause psychological health. This study analyzed the correlation between psychosocial factors and happiness. There are 10 psychosocial factor analyzed in this research. The data of this research has been collected by using descriptive statistics and Moderated Linear Regression method for statistical analytics. The result of this research shows that sense of community is experiencing psychosocial factors and that has a positive impact among other psychosocial factors. The happiness index level in PT. Kereta Api Indonesia Head Office in average is in Medium Level with 72,3%. And the most correlated psychosocial factor for happiness in millennial workers is organizational justice. It can be concluded that psychosocial factors have a correlation with the level of happiness for millennial workers at PT. Kereta Api Indonesia Head Office. Keyword:  Happiness, Happiness Index, Millennial generation, Psychosocial factors, PT. Kereta Api Indonesia Head Office.